If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3m + -1m = -4 Combine like terms: -3m + -1m = -4m -4m = -4 Solving -4m = -4 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-4'. m = 1 Simplifying m = 1
| 4x+1=9x-4 | | 10/1=n/5 | | X+6+ax-9=3x+b | | 9/3=n/9 | | 5/9=x/30 | | 18=k/3-2 | | 3x+8-9x=2x-16 | | -7(3x-7)+7x=14 | | 6.1(3.1+2.5)=15.3-3.9 | | 0.75x-12=0.5x-6 | | 7(3g+5K)-14g+12= | | 2b+2b=-16 | | 8-(1/2)y=-6 | | -3x-1=21 | | 0.75-12=0.50-6 | | B+4=3 | | 42x+21=90 | | 3m(2m+3)=0 | | 0.75+n=2 | | -8t^2+4t+12=0 | | ln(x)-ln(13)=0 | | -65/50 | | -3x+-1+-2=-9 | | 7x-4=5x-46 | | 50y/50 | | 108-1-4y=0 | | 50/50y= | | 2.48/4=x | | 9x+4-2x-2=16 | | .4x-(x+.3333333333)=.06666666666(x+1) | | 4(f+3)=17+4f | | -13b+b=31 |